Facile Solution Processing of Stable MXene Dispersions towards Conductive Composite Fibers. Issue 10 (15th July 2019) - Seyedin, Shayan; Zhang, Jizhen; Usman, Ken Aldren S.; Qin, Si; Glushenkov, Alexey M.; Yanza, Elliard Roswell S.; Jones, Robert T.; Razal, Joselito M.
Abstract: 2D transition metal carbides and nitrides called "MXene" are recent exciting additions to the 2D nanomaterials family. The high electrical conductivity, specific capacitance, and hydrophilic nature of MXenes rival many other 2D nanosheets and have made MXenes excellent candidates for diverse applications including energy storage, electromagnetic shielding, water purification, and photocatalysis. However, MXene nanosheets degrade relatively quickly in the presence of water and oxygen, imposing great processing challenges for various applications. Here, a facile solvent exchange (SE) processing route is introduced to produce nonoxidized and highly delaminated Ti3 C2 T x MXene dispersions. A wide range of organic solvents including methanol, ethanol, isopropanol, butanol, acetone, dimethylformamide, dimethyl sulfoxide, chloroform, dichloromethane, toluene, and n ‐hexane is used. Compared to known processing approaches, the SE approach is straightforward, sonication‐free, and highly versatile as multiple solvent transfers can be carried out in sequence to yield MXene in a wide range of solvents. Conductive MXene polymer composite fibers are achieved by using MXene processed via the solvent exchange (SE) approach, while the traditional redispersion approach has proven ineffective for fiber processing. This study offers a new processing route for the development of novel MXene‐based architectures, devices, and applications. Abstract : The rapid oxidation of MXene nanosheets in aqueous media imposes enormous processing challenges in the fabrication of MXene‐based structures and devices for desired applications. A sonication‐free solvent exchange processing approach that can achieve highly stable MXene in solution is introduced, and it is shown that MXene processed using the solvent exchange approach can be used to produce conductive composite fibers.